Dinamika Integrasi Pasar Volatilitas Harga dan Efektivitas Kebijakan Pemerintah dalam Stabilisasi Harga Beras di Sumatera Utara - Ginting, Nelva Meyriani; Sinaga, Anggiat; Gea, Sary (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2025)
Rice is a strategic commodity in North Sumatra, but its price volatility has the potential to hamper economic growth, disrupt poverty alleviation programmes, and reduce food stability. High rice prices indicate that government policies are not yet optimal, so price stabilisation is needed to ensure the availability and affordability of rice and support better distribution from producers to consumers. The purpose of this study is to analyse market integration, rice price volatility, rice price transmission, and government food policies for rice price stability in North Sumatra Province. The analysis methods used in this study are the Vector Error Correction Model (VECM) to analyse rice market integration, the ARCH/GARCH method to analyse rice price volatility, and the AECM (Asymmetric Error Correction Model) to analyse rice price transmission, and the Structural Equation Modelling (SEM) method to analyse government food policies for rice price stability in North Sumatra Province. The results of the study show that the rice market in North Sumatra is integrated in the long term, but remains weak in the short term with asymmetric price transmission. High price volatility occurs at the producer level, while it is relatively low at the consumer level due to government intervention. Government policies improve farmers' welfare but have a negative impact on price stability. Therefore, rice price stabilisation needs to focus on increasing productivity and improving food distribution to be sustainable and fair for consumers and farmers. Keywords: market, policy, price transmission, rice, volatility